Μετάφραση και σχοίασμός των άρθρων: '' Soccer emerges as the Gulf crisis potential icebreaker'' και '' Eyeing UK soccer clubs: Gulf buyers come with baggage'' του James M. Dorsey - (:unkn) unknown (My University, 2021)
Η παρούσα πτυχιακή εργασία βασίζεται στον σχολιασμό και τη μετάφραση δύο άρθων του James M. Dorsey. Αποτελείται από το εισαγωγικό κομμάτι, τα προτότυπα κείμενα, τα μεταφράσματα καθώς και τη κειμενική ανάλυση, τα μεταφραστικά προβήματα που προέκυψαν και τον τρόπο επίλυσης που επιλέχθηκε.

The following thesis is based on the commentary and translation of two articles by James M. Dorsey. It consists of the introductory part, the original articles, the translation as well as the analysis, the problems that arose and the solutions.
Keywords: Μετάφραση; Translation